Design and Analysis of Mechanism and Driving system for Manual Rice Transplantation Machine - Maharjan, Sanjeev; Regmi, Nipesh; Sapkota, Rama; Gupta, Saurabh; Bishwokarma, Durga (International Journal on Engineering Technology, 2025)
Novel design and fabrication of manual rice transplantation machine based on linkage dimension from Thomas to suit the cici4d varying terrains of Nepal and to initiate mechanization from the small land holders farmers are proposed in this study. The two row manual rice planter from Chandragiri Machiniery Industry, Satungal was taken as reference to modify transplanting mechanisms and driving systems to ease the rice plantation process. The optimum adjustable spacing of the rice seedlings is 20 to 25 cm hill to hill spacing and 10 cm row to row spacing. The depth of penetration of rice seedlings is also adjustable in this design. The power transmission for the driving mechanism is achieved through the traction power of the rice planting wheel. The capacity of rice transplanter is 270 sq. meters per hour which is equivalent to 5 number of manual hand rice transplanter workers. By cici4d using the proposed rice transplanter machine the total cost of hand rice transplantation can be reduced by approximately 75%.